Protection Against Simulating Interference Based on Coherent Storage and Pulsed Probing Signal with a Random Initial Phase - S. R. Heister; Huang Qianlan (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The confrontation between radar stations and radio electronic countermeasure systems leads to constant advancements on both sides as electronics continue to develop. This multifaceted confrontation determines the success of each side primarily based on the comprehensiveness of analysis and the correctness of the adopted system decisions. Occasionally, decisions are made in pursuit of quality, resulting in success in one aspect but failure in another. One such example is the transition to building radar stations based on true coherence principles. This work highlights the issue of protecting radar stations with true coherence from simulative interference. A method is presented for protecting against “near” simulative interference, which is the most dangerous and is generated between the radar stations and an aerial vehicle equipped with a radio electronic countermeasure systems. The method is based on combining an impulse probing signal with a random initial phase and coherent inter-period accumulation of the received signal.